The Impact of PRP Systems on Employee Motivation and Retention in the China Minsheng Bank - YI, KUNYANG (2014)
Abstract Purpose: With the changing environment, performance-related pay (PRP) has become an increasingly popular management tool to motivate and retain employee due to its strong incentive. However, it has been argued that the topic has not been researched sufficiently and there are also some detrimental effects of PRP. There remain gaps in knowledge within the academic literature about clarity of definitions and true evidence of positive outcomes. This study aims to examine the experiences of the introduction of PRP in the China Minsheng Bank in order to provide a perspective about how to motivate and retain the employees.